Person Organization Fit, Perceived Organizational Support and Organizational Citizenship Behavior: The Moderating Role of Job Embeddedness - Jufrizen, Jufrizen; Sianipar, Dahniar (International Journal Of Economics Social And Technology, 2023)
This research aims to determine and analyze the influence of a Person's Organizational Fit and Perceived Organizational Support on Organizational Citizenship Behavior moderated by Job Embeddedness. The approach used in this research is associative. The population in this study was 30 employees of the Medan City National Land Agency Office. In comparison, the sample in this study was 30 employees of the Medan City National Land Agency Office using a saturated sample. The data collection methods employed in this research encompassed the use of documentation, observation, and questionnaires. The research employs a quantitative approach to data analysis, utilizing statistical techniques such as Outer Model Analysis, Inner Model Analysis, and Hypothesis Testing. The research employs the PLS (Partial Least Square) software program for data processing. This research indicates that a Person's Organizational Fit and Perceived Organizational Support significantly influence Organizational Citizenship Behavior. Job Embeddedness moderates the influence of personal organizational Fit and Perceived Organizational Support on Organizational Citizenship Behavior at the Medan City National Land Agency Office